The Impact of the Urban Heat Island Effect on Ground-Level Ozone Pollution in the Sichuan Basin, China - Xingtao Song; Haoyuan Shi; Langchang Jin; Sijing Pang; Shenglan Zeng (Atmosphere)
With urbanization, ozone (O3) pollution and the urban heat island (UHI) effect have become increasingly prominent. UHI can affect O3 production and its dilution and dispersion, but the underlying mechanisms remain unclear. This study investigates the spatial and temporal distribution of O3 pollution and the UHI effect, as well as the influence of UHI on O3 pollution in the Sichuan Basin. Atmospheric pollution data for O3 and NO2 from 2020 were obtained from local environmental monitoring stations, while temperature and single-layer wind field data were sourced from ERA5-Land, a high-resolution atmospheric reanalysis dataset provided by the European Centre for Medium-Range Weather Forecasts (ECMWF). The results indicate the following: (1) O3 concentrations in the Sichuan Basin exhibit distinct seasonal variations, with the highest levels in spring, followed by summer and autumn, and the lowest in winter. In terms of spatial variation, the overall distribution is highest in western Sichuan, second highest along the Sichuan River, and lowest in central Sichuan. (2) There are significant regional differences in UHII across Sichuan, with medium heat islands (78.63%) dominating western Sichuan, weak heat islands (82.74%) along the Sichuan River, and no heat island (34.79%) or weak heat islands (63.56%) in central Sichuan. Spatially, UHII is mainly distributed in a circular pattern. (3) Typical cities in the Sichuan Basin (Chengdu, Chongqing, Nanchong) show a positive correlation between UHII and O3 concentration (0.071–0.499), though with an observed temporal lag. This study demonstrates that UHI can influence O3 concentrations in two ways: first, by altering local heat balance, thereby promoting O3 production, and second, by generating local winds that contribute to the diffusion or accumulation of O3, forming distinct O3 concentration zones.